2006
DOI: 10.1111/j.1399-6576.2006.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for failure to extend labor epidural analgesia to epidural anesthesia for Cesarean section*

Abstract: Younger, more obese parturients at a higher gestational week, requiring more top-ups during labor and having a higher VAS score in the 2 h before CS are at risk for inability to extend labor epidural analgesia to epidural anesthesia for CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…The success rate for conversion is high; however prolonged duration of labour analgesia, repeated need of clinician administered bolus doses and obesity are factors suggested to increase the risk of failure 20, 21 . Lidocaine with adrenalin with fentanyl supplementation is commonly used for conversion 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The success rate for conversion is high; however prolonged duration of labour analgesia, repeated need of clinician administered bolus doses and obesity are factors suggested to increase the risk of failure 20, 21 . Lidocaine with adrenalin with fentanyl supplementation is commonly used for conversion 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al 10 found that 93.5% of caesarean sections were performed under regional anaesthesia and 41% of pre-existing labour epidural catheters were used for caesarean section, reflecting the common practice of extending block in the presence of a functioning epidural catheter. We were careful to exclude parturients with recurrent breakthrough pain and those with recent intrapartum epidural supplementation, because these cases have been associated with a higher risk of failure to adequately extend labour analgesia 11 . Bupivacaine and levobupivacaine were found to have similar potency in both in vitro and in vivo studies 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies investigated the characteristics and predictive factors for failure of neuraxial anesthesia, 13,18 focusing on the failure of augmentation of labor epidural analgesia for CD. 19,20,24 Unfortunately, there is no standardized definition of epidural failure in the literature, which may explain the wide range of reported epidural failure rates. 25 Another reason for discrepancies may be including different types of failures such as epidural analgesia failure during labor or epidural anesthesia failure during CD.…”
Section: Discusssionmentioning
confidence: 99%